Wound healing activities of different extracts of Centella asiatica in incision and burn wound models: an experimental animal study - Somboonwong Juraiporn; Kankaisre Mattana; Tantisira Boonyong; Tantisira Mayuree H (BMC, 2012)
Abstract Background The efficacy of Centella asiatica for incision and burn wounds are not fully understood. Here, we report the wound healing activities of sequential hexane, ethyl acetate, methanol, and water extracts of Centella asiatica in incision and partial-thickness burn wound models in rats. Methods Male Sprague-Dawley rats weighing 250-300 g were randomly divided into incision and burn wound groups. Each group was stratified into seven subgroups: (1) untreated; (2) NSS-; (3) Tween 20®- (vehicle control); (4) hexane extract-; (5) ethyl acetate extract-; (6) methanol extract-; and (7) aqueous extract-treated groups. The test substances were applied topically once daily. The tensile strength of the incision wound was measured on the seventh day after wound infliction. The general appearance and degree of wound healing of the burn wound were assessed on Days 3, 7, 10 and 14 after burn injury and prior to histopathological evaluation. Results On the seventh day after wound infliction, the tensile strength of incision wound in all extract-treated groups was significantly higher than that of the vehicle control (Tween 20®), but comparable to the NSS-treated group. The degrees of healing in the burn wound with the four extracts were significantly higher than that of the control on Days 3, 10 and 14. Histopathological findings on Day 14 after burn injury revealed prominent fibrinoid necrosis and incomplete epithelialization in the control and untreated groups, whereas fully developed epithelialization and keratinization were observed in all extract-treated groups. Analysis by thin layer chromatography demonstrated that the phyto-constituents β-sitosterol, asiatic acid, and asiaticoside and madecassocide were present in the hexane, ethyl acetate and methanol extracts, respectively. Conclusions All extracts of Centella asiatica facilitate the wound healing process in both incision and burn wounds. Asiatic acid in the ethyl acetate extract seemed to be the most active component for healing the wound.